132. Age-Associated Abnormalities in Intrinsic Functional Connectivity Between the Amygdala and Ventromedial Prefrontal Cortex in Psychosis - Jalbrzikowski, Maria (Schizophr Bull, 2017)
Background: The ability to appropriately regulate one’s emotions is disrupted in psychosis. Connectivity between the amygdala and ventromedial prefrontal cortex (vmPFC) is integral for responding to emotions. In typically developing youth, functional connectivity between the amygdala and vmPFC subregions decreases from late childhood through adulthood. It is unknown to what extent age-associated amygdala-vmPFC functional connectivity is altered in psychosis. Methods: We examined age-associated differences in amygdala-vmPFC subregion functional connectivity using resting state fMRI in the Philadelphia Neurodevelopmental Cohort (PNC, 10–22 years, typically developing = 327, psychosis spectrum = 118, other psychopathology = 313) and in a separate, locally collected sample (12–36 years, first episode psychosis = 35, controls = 27). Regression models were used to assess Age × Group interactions in amygdala-vmPFC subregion connectivity. Linear, inverse, and quadratic effects of age were tested. Results: In the PNC, there was a significant inverse age by group interaction (t = 2.6, P = .01) between connectivity in the centromedial (CM) amygdala and rostral anterior cingulate (rACC). Expected age-associated decreases CM amygdala- rACC connectivity were observed in typically developing youth (r = −.19, P = .0004) and the other psychopathology group (r = −.18, P = .002). Psychosis spectrum youth (aged 10–14 years) showed similar connectivity; however, there was a failure to show decreases at older ages in CM amygdala-rACC connectivity (r = .09, P = .3). Similarly, there was a trend towards linear age*group interaction in the first episode psychosis versus controls sample (t = −1.9, P = .06). Parallel to the PNC cohort, controls exhibited significant age-associated decreases in CM amygdala–rACC connectivity (r = −.37, P = .05), and those with first-episode psychosis failed to show this age-associated decrease (r = .11, P = .55). Conclusion: Two independent cohorts show that individuals experiencing psychotic symptoms fail to show typical age-associated decreases in CM amygdala–rACC connectivity, regions important for the cognitive control of emotions. This age-related disruption may contribute to one’s inability to appropriately respond to psychotic symptoms, leading to increases in symptomatology. Thus, alterations in adolescent amygdala-vmPFC neurodevelopment may contribute to the emergence of psychosis.